THE ANALYSIS OF FACTORS AFFECTING ISLAMIC BANK FINANCING ON AGRICULTURAL SECTOR IN INDONESIA, PERIOD OF 2009-2015 - Nurul Fahma Amalia (EKPI 16 UMY 105, 2016)
This research examines the relationship between Financing on Agricultural Sector (FAS), and the internal and external factors of Islamic Bank. The internal factors are Non-Performing Financing on Agricultural Sector (NPFAS), Depositors Fund (DEPF), Capital Adequacy Ratio (CAR), and Return on Asset (ROA) and the external factor is Inflation (INF). The methodology used in this study to find the long-run relationship among those variables is Cointegration Test; and to find the short-run relationship among variables is Vector Error Correction Model (VECM). This study uses the monthly data within period of January 2009-June 2015. The result shows that there is cointegration (long-run relationship) among FAS, INF, NPFAS, DEPF, CAR, and ROA. Meanwhile, the VECM estimation shows that FAS is affected significantly negative by NPFAS. On the contrary, CAR influences FAS significantly positive. Lastly, INF, DEPF, and ROA influence FAS insignificantly. Keywords: Islamic Bank Financing, Financing on Agricultural Sector, Inflation (INF), Non-Performing Financing on Agricultural Sector (NPFAS), Depositors Fund (DPK), Capital Adequacy Ratio (CAR), and Return on Asset (ROA